Effect of Sucrose, Salicylic Acid (SA), Sulfosalicylic Acid (SSA), Silver Nano and Ajwain E.O on Vase Life of Single Tuberose (Polianthes tuberosa L.) - , Kumari Anjali; , Sunil Kumar; , Devendra Kumar; , Niranjan Singh; , Hitesh Kumar (Archives of Current Research International, 2024)
Tuberose is a highly valued flower known for its vibrant colors, elegance, and captivating fragrance. It is prominent in floral arrangements, both as a cut flower and in the perfume industry. Despite its visual appeal, tuberose flowers have a relatively short shelf life. To address this, researchers have explored various chemical treatments to enhance the longevity and quality of cut tuberose. An experiment was conducted at the Department of Floriculture and Landscaping, College of Horticulture & Forestry, Kumarganj, Ayodhya, during the 2023-24 period. The study, which followed a completely randomized design with sixteen treatments and three replications, aimed to determine the effects of different chemical solutions on the vase life of tuberose (Polianthes tuberosa L.). The results demonstrated significant differences among the treatments in various parameters, including changes in fresh weight, percentage change in spike length, longevity of the five basal florets (in days), vase solution uptake (in ml), vase life (in days), time taken for the first five florets to open, individual floret longevity, period of prime beauty, time taken for full spike opening, time for the first floret to fade, and time for the entire spike to fade. Among the treatments, the solution containing salicylic acid and sucrose proved to be the most effective in extending vase life. The combination of 2.5% sucrose, 50 ppm salicylic acid, and 150 ppm silver nanoparticles (T12) achieved the highest longevity for the five basal florets, lasting 4.75 days. Additionally, the treatment with 2.5% sucrose and 150 ppm silver nanoparticles (T8) resulted in 100% of florets opening. The longest vase life of 9.83 days was observed with the combination of 2.5% sucrose, 50 ppm salicylic acid, and 150 ppm silver nanoparticles (T12). This study underscores the effectiveness of specific chemical treatments in significantly improving the vase life and overall quality of cut tuberose flowers.